Decreased expression of TGF-β type II receptor in bronchial glands of smokers with COPD. Issue 12 (14th October 2005) - Baraldo, S; Bazzan, E; Turato, G; Calabrese, F; Beghé, B; Papi, A; Maestrelli, P; Fabbri, L M; Zuin, R; Saetta, M
Abstract : Background: The role of transforming growth factor-β1 (TGF-β1 ) in chronic obstructive pulmonary disease is still controversial, but it has been proposed that it may protect from mucus hypersecretion since it is able to downregulate mucin production. A study was undertaken to investigate the expression of TGF-β1 and its type II receptor (TGF-β RII) in the bronchial glands of smokers with COPD. Methods: The expression of TGF-β1 and TGF-β RII were examined immunohistochemically in the bronchial glands of 24 smokers undergoing lung resection for solitary peripheral nodules: 12 with airflow limitation (smokers with COPD) and 12 with normal lung function. Results: The expression of TGF-β1 in bronchial glands was similar in the two groups of subjects while that of TGF-β RII was lower in smokers with COPD than in smokers with normal lung function (p = 0.004). TGF-β RII expression was inversely correlated with the values of Reid's index, a measure of gland size (p = 0.02, r  = −0.50). Conclusions: In the bronchial glands of smokers with COPD there is decreased expression of TGF-β RII which is associated with bronchial gland enlargement. These findings support the view that the absence of TGF-β signalling may induce structural changes in the bronchial glands which, in turn, may promote mucus hypersecretion.